2020
DOI: 10.5539/ies.v13n8p79
|View full text |Cite
|
Sign up to set email alerts
|

Interest in Extra Curricular Activities and Self Efficacy of Senior Secondary School Students in Cross River State, Nigeria

Abstract: The main purpose of the study was to find out if interest in extra-curricular activities has any influence on self-efficacy with reference to social self-efficacy, academic self-efficacy, language self-efficacy and moral self-efficacy. The ex-post facto design was adopted for the study. A sample of 1,586 students was randomly selected from the public secondary schools in Cross River State for the study. A questionnaire titled “Interest in Extra Curricular Activity and Self-Efficacy (IECASEQ) was the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 21 publications
2
9
0
Order By: Relevance
“…However, Denault & Poulin (2009) reported that participation in performing arts and academic clubs can be linked to higher academic grades than participation in sports while Villarreal (2013) reported that participation in sports accords students a sense of school belonging and social interactions among students, parents and school. This is corroborated by Bekomson et al (2020) who suggest that taking part in interesting physical activities as part of an ECA can promote the mental alertness of students and lead to academic attainment. Regarding the attainment of students, Chan et al (2020) reported that math-focused out-of-school time support can have a positive impact on students' attainment than ASSC.…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…However, Denault & Poulin (2009) reported that participation in performing arts and academic clubs can be linked to higher academic grades than participation in sports while Villarreal (2013) reported that participation in sports accords students a sense of school belonging and social interactions among students, parents and school. This is corroborated by Bekomson et al (2020) who suggest that taking part in interesting physical activities as part of an ECA can promote the mental alertness of students and lead to academic attainment. Regarding the attainment of students, Chan et al (2020) reported that math-focused out-of-school time support can have a positive impact on students' attainment than ASSC.…”
Section: Introductionmentioning
confidence: 66%
“…Other studies have constructed their frameworks around the ownership of the various ECAs and the implications for perceived gains of ECA. This includes the impact of ECAs on selfefficacy (Attarwala, 2015;Raffo & Forbes, 2020;Bekomson et al, 2020), academic and learning outcomes (Storey, 2010;GEC, 2018;Behtoui, 2019;Donnelly et al, 2019), impact on peer interaction, social capital, and friendships (Fredricks & Simpkins, 2012;Simpkins, Vest, Delgado, & Price, 2012), teamwork, social skills, managing emotions (Braund & Reiss, 2006;Siddiqui, Gorard & See, 2019;Buckley & Lee, 2021) and resilience (Raffo & Forbes, 2020).…”
Section: Theoretically Framing the Literature On Extra-curricular Act...mentioning
confidence: 99%
“…Self-efficacy refers to the beliefs in one's capabilities to produce appropriate actions in managing prospective situations. In line with that, a study by Bekomson et al [19] suggested that extra-curricular activities positively relate to selfefficacy, as when students involved in extra-curricular activities, they were exposed to challenging situations that provided them opportunities to develop characters such as self-efficacy, perseverance, and locus of control.…”
Section: Schoolmentioning
confidence: 84%
“…Extracurricular activities refer to students' non-academic activities and fall outside the institution's curriculum (Khanna et al, 2020). Interest in extracurricular activities was found to significantly influence social, academic, linguistic, moral, and overall self-efficacy (Bekomson et al, 2020).…”
Section: Extracurricular Activities and Thinking Stylesmentioning
confidence: 95%